MATHEMATICAL MODEL OF DETERMINATION OF AIR COSTS FOR THE POLYTROPIC PROCESS DURING THE SEALING OF AN AIRCRAFT COMPARTMENT - Доник, В. Д. (Proceedings of National Aviation University (archive), 2021)
A mathematical model for determining air flow for the polytropic process of air leakage from the volume has been developed. The characteristics of the model are investigated. The adequacy of the developed model to the real process is determined.